The unexpected versatility of ALP/Enigma family proteins - Fisher, Lucas A. B.; Schöck, Frieder (Frontiers in Cell and Developmental Biology, 2022)
One of the most intriguing features of multicellular animals is their ability to move. On a cellular level, this is accomplished by the rearrangement and reorganization of the cytoskeleton, a dynamic network of filamentous proteins which provides stability and structure in a stationary context, but also facilitates directed movement by contracting. The ALP/Enigma family proteins are a diverse group of docking proteins found in numerous cellular milieus and facilitate these processes among others. In vertebrates, they are characterized by having a PDZ domain in combination with one or three LIM domains. The family is comprised of CLP-36 (PDLIM1), Mystique (PDLIM2), ALP (PDLIM3), RIL (PDLIM4), ENH (PDLIM5), ZASP (PDLIM6), and Enigma (PDLIM7). In this review, we will outline the evolution and function of their protein domains which confers their versatility. Additionally, we highlight their role in different cellular environments, focusing specifically on recent advances in muscle research using Drosophila as a model organism. Finally, we show the relevance of this protein family to human myopathies and the development of muscle-related diseases.